Фізичні властивості монокристалів g-фази взаємної системи CuInSe2 + 2CdТеÛ CuInТе2 + 2CdSe - Олексеюк, И. Д.; Olekseyuk, I. D.; Лавринюк, З. В.; Lavrynyuk, Z. V.; Парасюк, О. В.; Parasyuk, O. V.; Юрченко, О. Н.; Yurchenko, O. N.; Змий, О. Ф.; Zmiy, O. F (Волинський національний університет ім. Лесі Українки, 2010)
Исследованы физические свойства монокристаллов g-фазы, выращенных модифицированным методом Бриджмена по сечению CuInSe2− 2CdTe системы CuInSe2 + 2CdTe Û CuInTe2 +2 CdSe. Определена ширина запрещенной зоны этих кристаллов по спектрам поглощения. Электрические свойства кристаллов определяли измерениями эффекта Холла и температурной зависимости проводимости кристаллов. The physical properties of the single crystals of the g-phase grown by modified Bridgman method of the CuInSe2 + 2CdTe ÛCuInTe2 + 2CdSe system have been investigated. The band gap of these crystals from the absorption spectra was defined. The electrical properties of the crystals were determined by measuring the Hall effect and temperature dependence of the crystal conductivity.
The Phisycal Properties of the γ-Phase Single Crystals of the Reciprocal System CuInSe2 + 2CdTe ÛCuInTe2 + 2CdSe
Keywords: халькогениды; the phase diagrams; фазовая диаграмма; band gap; кристаллическая структура; chalcogenide semiconductors